Burdens of Gastroesophageal Reflux Disease in China: Findings from the 2021 GBD Study - Zhiqiang Liang; Zehui Hou; Zhuomin Yu; Bing Zeng; Fang Li; Jingjing Wu; Yingru Li; Zhipeng Jiang (PLoS ONE, 2025)
As a major global health concern, Gastroesophageal Reflux Disease (GERD) has garnered widespread attention; However, to date, the prevalence of GERD across different ethnic groups in China has not been comprehensively examined by any large-scale epidemiological studies or meta-analyses. Against this backdrop, the present study draws on data from the Global Burden of Disease (GBD) Study to investigate the burden of GERD in China. Data from the 2021 GBD Study were utilized to assess the burden of GERD in China, focusing on key indicators such as prevalence, incidence, Years of Life Lived with Disability (YLDs), Age-Standardized Rates (ASR). Health inequality analyses were used to measure the inequality in the distribution of GERD across countries based on the Socio-Demographic Index (SDI), as well as to determine whether such inequality exists in China. Frontier analysis identified top performers in healthcare systems across different countries when examining the burden of GERD, followed by a comparison of differences in GERD burden between China and these top-performing countries. The trends of GERD from 2022 to 2044 were projected using the Nordpred and ARIMA model. Between 1990 and 2021, the prevalence of GERD in China experienced a notable rise of 60.62%. Correspondingly, the ASR also increased significantly. A similar pattern was Observed in incidence and YLDs, with number and ASR rising. A frontier analysis revealed that China had relatively low prevalence and incidence rates but a moderate-to-high level of SDI. Health inequality analysis revealed both absolute and relative inequalities related to SDI, with a noticeable increase in the inequality of the age-standardized GERD burden from 1990 to 2021. a significantly greater inequality in GERD burden was observed in China compared to other countries, suggesting a disparity in GERD distribution relative to SDI. Projections of GERD in China extending from 1990 to 2044 indicate a steady increase in the combined numbers and ASR of prevalence, incidence, and YLDs. The disease burden of GERD in China has risen steadily over the past three decades, with marked increases in the ASRs of its prevalence, incidence, and YLDs. Given the growing number of individuals affected by GERD, adapting healthcare systems to address the escalating demand for related services and treatments has become an urgent necessity.